Arbitration costs : myths and realities in investment treaty arbitration - Franck, Susan D. (New York, NY : Oxford University Press, 2019)
Investment treaty arbitration has become a flashpoint in the backlash against globalization, with costs becoming an area of core scrutiny. Yet 'conventional wisdom' about costs is not necessarily wise. To separate fact from fiction, this text reality tests claims about investment arbitration & fiscal costs against hard data so that policy reforms can be informed by scientific evidence, rather than intuition or cognitive illusions. The exercise is critical, as investment treaties grant international arbitrators the power to order states - both rich & poor - to pay potentially millions of dollars to foreign investors when states violate the international law commitments made in the treaties. Meanwhile, the cost to access & defend the arbitration can also be in the millions of dollars. This text examines this topic.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 15, 2019).
Keywords: Investments, Foreign -- Law and legislation; Investments, Foreign (International law); International commercial arbitration; Commercial treaties; Law; Laws of specific jurisdictions & specific areas of law